Experimental Study and Simulation on the Seal Pressure of a Ferrofluid Seal Using Radial-Charged Magnets - Liu, Jiawei; Li, Decai; Zhang, Zhili (Frontiers in Materials, 2022)
As one of the most mature applications of ferrofluid, the pole shoes of ferrofluid seal are easily damaged under the situation of the large radial beating of the main shaft. Meanwhile, due to the small size, the pole teeth commonly used in pole shoes harbors problems such as poor processablity and low seal pressure under a large gap.In order to solve the problems above, we proposed the new structure of the ferrofluid seal that uses radial-charged ring magnet as the magnetic source. Then considering that the ring magnets have problems of uneven magnetization and installation difficulties, we used split magnets to take the place of ring magnets and proposed the second new structure.According to the study on the distribution of magnetic field in seal gap axially and circumferentially, we got the simulation results of the two new structures’ seal pressure. The results revealed that the new structure of ferrofluid seal with rectangular magnets can solve the problems above and exhibited a certain amount of sealing pressure.